How difficult is it to diagnose and report an occupational disease in a developing country? A modified delphi study - Karabağ, İlke; Alagüney, Mehmet Erdem; Şahan, Ceyda; Yıldız, Ali Naci (Acta Medica, 2023)
Aim: The roles of occupational medicine specialists are very important in the diagnosis and notification of occupational diseases. In this regard, the opinions of the parties are needed to identify the problems and propose solutions. Methods: This is a Modified Delphi exercise. It was conducted through an online survey in 2 rounds in Turkey between June 4, 2021 and August 31, 2021. The population of the research consists of occupational medicine specialists and sub-branch students in Turkey and some physicians working in the central organizational units of the Ministry of Health and the Ministry of Labor and Social Security regarding the diagnosis, registration and notification of occupational diseases. In both rounds, e-mails were sent to 127 people. The survey was sent via , and the response frequency was 27.5% and 18.1% in rounds 1 and 2, respectively. A survey form was created for the second round by evaluating the open-ended information obtained as a result of the first round using the thematic analysis method and making suggestions. This form was sent to participants via e-mail and questions were asked about participation in the proposals in the second round. Proposals with 70% or more participation were accepted unanimously. Results: The most important difficulties regarding the diagnosis and details of occupational diseases are; The lack of a national occupational disease surveillance system, the fact that the current occupational disease diagnosis and summary system is focused on pricing, and the difficulties people experience in diagnosis were determined. Conclusion: In order to increase the reporting of occupational diseases, a surveillance-oriented system should be switched instead of a compensation-based system. In addition, the deficiencies in manpower, financing, technical infrastructure and legislation in the occupational disease reporting system need to be rapidly revised.